Expression of cell-cycle-dependent genes in phytohemagglutinin-stimulated human lymphocytes. - Kaczmarek, L (1985)
We have investigated the expression of certain cell-cycle-dependent genes in human peripheral blood mononuclear cells (PBMC) stimulated by phytohemagglutinin (PHA). The genes studied had been previously identified as cell-cycle dependent in other cell types from different species and were induced by different mitogens. One of these genes (2F1) and the gene for the interleukin 2 receptor were induced by PHA even in cultures partially depleted of accessory cells where the lymphocytes grew in size but failed to enter S phase. The other genes (c-myc, 4F1, JE-3, and KC-1) were induced only in complete cultures of PBMC stimulated by PHA. These results confirm the dissociation between growth in size and cell DNA replication that can occur during cell-cycle progression. Moreover, the time course of appearance of detectable levels of RNA for these genes suggests that they may be used as markers of cell-cycle progression in the transition of lymphocytes from G0 to S phase.